BIOLOGIK FAOL QO`SHIMCHA MAHSULOTLARNING TURLARI VA ULARNI SPORTDA QO`LLASH TAMOYILLARI - Mamutov, P.J. (SCIENCE and SOCIETY, 2021)
The article describes in detail the introduction of dietary supplements in the diet of athletes, the regulation of nutrition, nutrients in the body, and the introduction of a balanced diet in accordance with the concept of nutrients and energy. There is also an understanding of the physiological needs of the body for nutrients during illness, the restoration of metabolically damaged organs in the pathological process, the effectiveness of biologically active substances and their effect on the athlete's body. The article is moderately abstract and is undoubtedly the first step in future experimental research.
Keywords: sport; healthy lifestyle; physical education; pharmacology; rehabilitology; dietetics